Electronic Structure, Optical and Sensor Properties of ZnO Nanowires - O.V. Bovgyra; M.V. Kovalenko (Журнал нано- та електронної фізики)
Density functional theory calculations of structural, electronic and optical properties of nanowires ZnO were performed. The obtained results are showing that the band gap increase with the decrease of the ZnO nanowire size. The calculated ZnO nanowires dielectric function shows a significant blueshift with those of bulk ZnO. Our results give some reference to the thorough understanding of optical properties of ZnO, and also enable more precise monitoring and controlling during the growth of ZnO materials to be possible. Also theoretical calculations of adsorption of the different gases molecules on side of nanowires ZnO were performed. Their charge transfer to the nanowire sidewall is investigated in order to determine the donor or acceptor character of molecular adsorbing.